Living a Cosmopolitan Curriculum: Civic Education, Digital Citizenship, and Urban Priority Schools - Gladu, Jessica (Université d'Ottawa / University of Ottawa, 2021)
The reason for my research is that youth who experience marginalization do not have their experiences represented in their civics classrooms, which leads to a lack of civic engagement overall (Kane, Ng-A-Fook, Radford & Butler, 2017; Claes, Hooghe, and Stolle, 2009). I identify cosmopolitanism (Hansen, 2010; Banks, 2009; Pinar, 2009) and pedagogies of digital citizenship (Choi, 2016; Coleman, 2008) as potentially useful orientation and processes to better support marginalized youth in Urban Priority High Schools (UPHS). In this study, I use discourse analysis to analyse the “curriculum as plan[ned]” (Ontario Ministry of Education civic curriculum documents) with and against the narrative inquiry of the “lived curriculum” in an Urban Priority High School (Aoki, 1993; 2003). The findings of my study include that although the Ontario grade 10 civics curriculum (Ontario Ministry of Education, 2018) has possibilities of a cosmopolitan orientation because of some of the language used and concepts introduced in the Citizenship Education Framework and goals, this curriculum cannot be considered cosmopolitan. There are no overall or specific expectations that have students consider their own identity formation and subjectivity (Pinar, 2009), reflective openness (Hansen, 2010), and cultural, national and global identifications (Banks, 2009). While the curriculum as planned was found to be lacking in expectations that align with cosmopolitanism, the findings of my study underscored how digital citizenship projects that invite students to grapple with issues of significance of the self and the Other open up productive spaces of civic engagement for marginalized students. Digital spaces allowed students to narrate their lived experiences that underscored the significance of embracing a cosmopolitan identity in a mandatory course that otherwise does not serve them and illustrates the urgency of these curriculum opportunities if education is working in the name of equity and supporting each youth to become active citizens.
Keywords: Cosmopolitanism; Civic education